Performance Optimisation of Axial Field Partitioned Stator Switched Flux PM Machine with Spoke-type PM Stator - Mohammed F. H. Khatab; Abubaker A. Saed (African Journal of Advanced Pure and Applied Sciences, 2026)
An axial field switched flux permanent magnet (AFSFPM) machine shows favourable production by integrating the benefits of both switched flux permanent magnet (SFPM) and axial field permanent magnet (AFPM) Machines. An axial-field partitioned stator switched-flux permanent magnet (AFPS-SFPM) machine was introduced, and the machine was optimised for maximum electromagnetic torque. This study examines the impact of PM shape on the performance of AFPS-SFPM machine. Surface-mounted PM was used for the basic machine stator. However, the machine is equipped with a flux-focusing permanent magnet stator (Spoke type stator). The design has been optimised and compared to the basic design. The results show that using a spoke-type PM stator significantly improved the machine’s no-load performance. Moreover, the machine with spoke-type PM stator produces about 60% more torque than the machine with a surface-mounted PM stator. However, the proposed topology has a larger PM volume than the basic topology.